In-vitro analysis of maxillary first molars morphology using three dimensional Micro-CT imaging: considerations for restorative dentistry - Kaan Orhan; Mehmet Eray Kolsuz; Gülbike Demi̇rel; İsmail Hakkı Baltacıoğlu (Istanbul University, 2018)
DOI: 10.26650/eor.2018.448Purpose The aim of this study was to determine the differences between the positional relationship of the crown contour and the pulp chamber of left and right maxillary first molars, as well as their morphological characteristics by using micro-CT system with reconstruction from a volumetric rendering software. Materials and methods In total, 21 extracted maxillary first molars, including 11 left and 10 right teeth, were used. The positional relationship between the crown contour, pulp chamber and morphology of the teeth were investigated three-dimensionally by means of micro-CT imaging. Results Closest distance of mesio-buccal pulp horn to enamel surface in mm was calculated as 2.5±0.20 mm for right and 2.29±0.17 mm for left teeth. This difference was statistically significant (p=0.017). The means of closest distance of disto-buccal pulp horn to enamel surface were also significantly different between left and right teeth (p=0.001). The mean pulp volumes of right side and left side teeth were, respectively, 32.94±3.19 mm3 and 33.71±2.82 mm3 but this difference was not statistically significant. Conclusion These results suggest that right and left maxillary first molars should be treated differently during preparation of cavities. Further studies must be done with larger samples as well as for other molar teeth in different populations to reveal the morphology of the molar for further considerations in restorative dentistry.